2022
DOI: 10.3390/molecules27041204
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Biological Activity of Anthraquinons and Flavanoids of the Plant Rumex Species

Abstract: Rumex confertus belongs to the genus Rumex and is classified as an invasive parasitic plant in agriculture. Despite other Rumex species being widely used in herbal medicine due to their antimicrobial, antioxidant, antitumor, and anti-inflammatory effects, there are almost no information about the potential of Rumex confertus for the treatment of various diseases. In this review we analyzed scientific articles revealing properties of Rumex plant’s substances against cancer, diabetes, pathogenic bacterial invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 106 publications
0
5
0
1
Order By: Relevance
“…The content of phloroglucinol derivatives in eucalyptus leaf residue accounted for 1.93% of the raw material. Research has shown that phloroglucinol derivatives have good biological activities such as antibacterial, antiviral, and anti-tumor effects, with broad prospects for medical research, and are expected to become new anti-tumor and antibacterial drugs [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The content of phloroglucinol derivatives in eucalyptus leaf residue accounted for 1.93% of the raw material. Research has shown that phloroglucinol derivatives have good biological activities such as antibacterial, antiviral, and anti-tumor effects, with broad prospects for medical research, and are expected to become new anti-tumor and antibacterial drugs [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Perception of nitrogen deficiency and generation of the nitrogen starvation signal are accompanied by attraction of rhizobia to the plant root. This step, in turn, relies on the synthesis and excretion of flavonoids, which act as the signaling molecules secreted by root cells [25,26] (Figure 2). These polyphenols probably belong to the group of chemoattractants for rhizobia, which also include amino acids-e.g., glutamate, proline, arginine, phenylalanine, tryptophan [27,28], and carboxylates, like citrate, malate, and succinate [29,30].…”
Section: Mutual Recognition: Flavonoids As the Attractants For Rhizobiamentioning
confidence: 99%
“…fruit extracts and its oil [ 95 ], extracts of Thymus serpyllum L. [ 96 ], extracts of Rumex confertus Willd. leaves [ 97 ], mulberry root bark extracts [ 98 ], Pleurotus ostreatus (Fr.) [ 99 ], castor bean leaf extracts [ 100 ].…”
Section: Anti-neurodegenerative Properties Of Medicinal Plants and Th...mentioning
confidence: 99%